Whole exome sequencing identifies a mutation in thrombomodulin as the genetic cause of a suspected platelet disorder in a family with normal platelet function - Annabel Maclachlan; Gerry Dolan; Charlotte Grimley; Steve P. Watson; Neil V. Morgan; on behalf of the UK GAPP Study Group (Platelets, 2017)
Here, we describe a mother and son with a lifelong bleeding tendency and posttraumatic bleeding who were recruited to the UK Genotyping and Phenotyping of Platelets (GAPP) study with a suspected platelet function disorder. However, despite a clinically significant bleeding score, both had normal platelet counts and normal platelet function. The patients’ blood was analyzed by light transmission aggregometry and genotyping by whole exome sequencing, as outlined by the GAPP study. Approximately 25 000 genetic variants were found for each patient as a result of sequencing and were filtered using a specialized bioinformatics pipeline. A heterozygous variant displaying autosomal dominant inheritance (c.1611 C>A) was found in the gene THBD which encodes the glycoprotein thrombomodulin. This sequence change results in a stop codon (p.Cys537Stop) and truncation of the protein and has been previously described in two other families with bleeding events which suggests it may be a recurrent mutation. In summary, this study shows that patients with a suspected platelet disorder but who present with a normal pattern of platelet aggregation should be investigated for defects in nonplatelet genes.